2016
DOI: 10.1188/16.onf.e188-e194
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Experience and Perceived Changes in Siblings of Children With Cancer Reported During a Group Intervention

Abstract: Methodologically, this study demonstrated that the inclusion of visual materials as data is a valid methodology for future research. Clinically, these findings can help nurses in their daily care of children with cancer and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 30 publications
1
60
0
4
Order By: Relevance
“…D'Urso, Mastroyannopoulou, and Kirby (2017) found that siblings experienced a variety of difficult emotions such as shock, fear, and uncertainty, especially at the time when their brother or sister was diagnosed with cancer. Some siblings expressed feeling left out from their own family or the ill child's cancer treatment itself (Neville et al, 2016), whereas others became increasingly withdrawn over the course of the cancer journey . O'Shea, Shea, Robert, and Cavanaugh (2012) also found that siblings displayed feelings of jealousy toward the ill child, making statements that the ill child received more parental attention, toys, food, gifts, and television time.…”
Section: An Array Of Emotional Changesmentioning
confidence: 99%
See 4 more Smart Citations
“…D'Urso, Mastroyannopoulou, and Kirby (2017) found that siblings experienced a variety of difficult emotions such as shock, fear, and uncertainty, especially at the time when their brother or sister was diagnosed with cancer. Some siblings expressed feeling left out from their own family or the ill child's cancer treatment itself (Neville et al, 2016), whereas others became increasingly withdrawn over the course of the cancer journey . O'Shea, Shea, Robert, and Cavanaugh (2012) also found that siblings displayed feelings of jealousy toward the ill child, making statements that the ill child received more parental attention, toys, food, gifts, and television time.…”
Section: An Array Of Emotional Changesmentioning
confidence: 99%
“…Siblings also experienced stress related to the cancer experience, adding significantly to the stressors already present in these children's daily lives (Neville et al, 2016). Furthermore, many siblings not only expressed grief, but also guilt as they considered that their brother or sister had a potentially terminal disease and might die (Jenholt nolbris et al, 2014).…”
Section: An Array Of Emotional Changesmentioning
confidence: 99%
See 3 more Smart Citations